Navigation in Space by X-ray Pulsars - Emadzadeh, Amir Abbas; Speyer, Jason Lee (Springer New York : Imprint: Springer, 2011)
This monograph on different aspects of utilizing X-ray pulsars for navigation of spacecraft in space contains two unique features. First, it provides a solid mathematical formulation for the absolute and relative navigation problems based on use of X-ray pulsar measurements. Second, it presents a comprehensive framework for signal processing techniques needed to obtain the navigation solution. Navigation in Space by X-ray Pulsars opens with background knowledge on pulsars and a review of the literature on pulsar-based navigation. It then presents the navigation problem and develops the X-ray pulsar signal models, formulating and analyzing the pulse delay estimation problem through these models. It proposes different pulse delay estimators and, using these estimators, provides a recursive algorithm to obtain the navigation solution. Closing with suggestions for future work in the field, this monograph is aimed at students, researchers and industry practitioners involved with new space navigation techniques.